Unfolded Protein Response in Lung Health and Disease - Barabutis, Nektarios (Frontiers in Medicine, 2020)
The Unfolded Protein Response (UPR) is a complex element, destined to protect the cells against a diverse variety of extracellular and intracellular challenges. UPR activation devises highly efficient responses to counteract cellular threats. If those activities fail, it will dictate cellular execution. The current work focuses on the role of UPR in pulmonary function, by immersing into the highly interrelated network that operate towards the endothelial barrier function. A highly sophisticated UPR manipulation shall reveal new therapeutic possibilities against inflammatory lung disease, such as Acute Lung Injury and Acute Respiratory Distress Syndrome.